Validity and reliability of the CatWalk system as a static and dynamic gait analysis tool for the assessment of functional nerve recovery in small animal models - Kappos, Elisabeth A.; Sieber, Patricia K.; Engels, Patricia E.; Mariolo, Alessio V.; D'Arpa, Salvatore; Schaefer, Dirk J.; Kalbermatten, Daniel F. (Brain and behavior, 2017)
Introduction A range of behavioral testing paradigms have been developed for the research of central and peripheral nerve injuries with the help of small animal models. Following any nerve repair strategy, improved functional outcome may be the most important evidence of axon regeneration. A novel automated gait analysis system, the CatWalk™, can measure dynamic as well as static gait patterns of small animals. Of most interest in detecting functional recovery are in particular dynamic gait parameters, coordination measures, and the intensity of the animals paw prints. This article is designed to lead to a more efficient choice of CatWalk parameters in future studies concerning the functional evaluation of nerve regeneration and simultaneously add to better interstudy comparability. Methods The aims of the present paper are threefold: (1) to describe the functional method of CatWalk gait analysis, (2) to characterize different parameters acquired by CatWalk gait analysis, and to find the most frequently used parameters as well as (3) to compare their reliability and validity throughout the different studies. Results In the reviewed articles, the most frequently used parameters were Swing Duration (30), Print Size (27), Stride Length (26), and Max Contact Area (24). Swing Duration was not only frequently used but was also the most reliable and valid parameter. Therefore, we hypothesize that Swing Duration constitutes an important parameter to be chosen for future studies, as it has the highest level of reliability and validity. Conclusion In conclusion, CatWalk can be used as a complementary approach to other behavioral testing paradigms to assess clinically relevant behavioral benefits, with the main advantage that this system demonstrates both static and dynamic gait parameters at the same time. Due to limited reliability and validity of certain parameters, we recommend that only the most frequently assessed parameters should be used in the future. A range of behavioral testing paradigms have been developed for the research of peripheral nerve injuries by small animal models. Following any nerve repair strategy, improved functional outcome may be the most important evidence of axon regeneration. The CatWalk can measure dynamic as well as static gait patterns of small animals in different study settings. This article is designed to lead to a more efficient choice of parameters in future studies concerning the functional evaluation of peripheral nerve regeneration to add to better interstudy comparability.